Preoperative Expectations of Patients Undergoing Knee Surgery - Stevens, Kali N.; Nadarajah, Vidushan; Jauregui, Julio J.; Song, Xuyang; Medina, Shaun H.; Smuda, Michael P.; Packer, Jonathan D.; Henn, R. Frank, 3rd (The Journal of Knee Surgery, 2019)
There is limited validated data regarding the relationship between preoperative expectations and patient-reported outcomes (PROs) in patients undergoing knee surgery. The purpose of this study was to (1) assess the preoperative expectations of patients undergoing knee surgery and (2) determine the relationship between preoperative patient demographics, PROs, and preoperative patient expectations. We hypothesized that younger patients with worse function and worse general health status would have greater expectations of knee surgery. We analyzed data from 399 patients undergoing knee surgery at an urban academic medical center. We utilized the Musculoskeletal Outcomes Data Evaluation and Management System to measure preoperative expectations. Multiple legacy PRO measures were recorded, as well as the new Patient-Reported Outcomes Measurement Information Systems (PROMIS) Computer Adaptive Testing. Nonparametric statistical analyses were performed to determine significance. Overall, patients undergoing knee surgery had high expectations, with a mean of 88.0 (95% confidence interval [CI], 86.7–89.3) and median of 91.7 (95% CI, 89.2–94.3). Greater preoperative expectations of knee surgery were associated with higher income, surgically naïve knee, lower Charlson Comorbidity Index, better PROMIS Depression and Anxiety scores, greater Marx knee activity scores, and lower total body pain (p < 0.05). Preoperative expectations of patients undergoing knee surgery are associated with a history of prior knee surgery, income, general and mental health, activity, and pain. Expectations were also found to be associated with PRO measures of function and psychological well-being. These findings may have implications for patient education and shared decision-making preoperatively. The level of evidence for the study is IV.
Keywords: PROMIS; patient expectations; knee surgery; patient-reported outcomes